Factors influencing Indonesian male partners’ support in the postpartum period - Agil, Hilda M; Watanabe, Kumi; Tanaka, Emiko; Afiyanti, Yati; Anme, Tokie (UI Scholars Hub, 2019)
Background: Lack of male partners’ postpartum support can cause postpartum depression (PPD), a serious mood disorder, in women. Thus, to prevent PPD, it is important to clarify the factors influencing male partners’ postpartum support. Methods: In total, 62 male partners of postpartum women at 1 week–6 months after delivery, living in South Jakarta, were invited by assistance from community volunteers. Focus group interviews were employed; participants were grouped depending on their residences and asked about their behaviors in supporting postpartum women. Interviews were documented using two voice recorders and two video recorders. The content analysis method and Bertalanffy’s system theory of internal and external factors of health behaviors was utilized to develop units and codes. Results: The analysis identified five codes of individual-level factors: (1) knowledge; (2) belief; (3) social and life adaptation skills; (4) psychological disposition; and (5) physiological condition. Three codes of community-level factors included: (1) social support; (2) media; and (3) socio-cultural and economic. Two codes of social policy-level factors included (1) health care system and; (2) Indonesian societal laws and regulations. Conclusions: Various internal and external factors influence Indonesian male partners’ postpartum support. Different interventions for these factors might be impactful in preventing PPD.